Representasi Emosi dan Strategi Bahasa Tokoh Livia dalam Representasi Emosi dan Strategi Bahasa Tokoh Livia dalam Film Winter Elegy dengan Tinjauan Psikolinguistik - Pasaribu, Nazwa Salsabila; Daely, Apriliani; Lubis, Nayla Apriani; Annisa, Nurul; Aini, Retno Anggelica; Barus, Frinawaty Lestarina (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to describe the emotional representation of the character Livia and analyze the language strategies used in the film Winter Elegy through psycholinguistic studies. The study uses a qualitative approach with descriptive methods. Data in the form of Livia's speech containing emotional content were obtained through document study techniques and non-participant observation. The data were analyzed through stages of reduction, coding, classification based on Silvan S. Tomkins' basic emotion theory, then interpreted using Willem J. M. Levelt's speech production theory to reveal the relationship between emotions and language processes. The results show that from 31 speech data, four types of emotions were found, namely Interest/Excitement, Enjoyment, Surprise/Startle, and Distress/Anguish. Interest/Excitement and Surprise/Startle emotions dominate throughout the process of seeking truth, while Distress/Anguish reaches its peak at the stage of accepting loss. The most dominant language strategy is the articulation stage, followed by formulation, while conceptualization and self-monitoring appear in certain emotional situations. This research provides a scientific contribution by integrating Tomkins's theory of emotion and Levelt's speech production model to explain the relationship between affective aspects and linguistic processes in the representation of female characters in Indonesian films, thereby enriching psycholinguistic studies in the analysis of audiovisual works